Implementation of Performance Management Based on Deming Model in PT. Bintan Jaya Samudra - Amoi Sarmila; Angelina Angelina; Ibra Maulana; Mita Fharissa Fhutri; Satriadi Satriadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to describe and analyze the implementation of Deming Model-based performance management (PDCA) in PT. Bintan Jaya Samudra. The research uses a type of descriptive research with a qualitative approach. Data collection was carried out through observation and interviews. The sample used was purposive sampling. The informant in this study is Mr. Ruslan Jumas as the president director of PT. Bintan Jaya Samudera. The data analysis used in this study uses descriptive analysis using triangulation techniques and sources. The company plans by emphasizing discipline and carrying out internal training for each employee which has then been carried out and will later be evaluated periodically and followed up. The results of the study show that the implementation of the Deming Model in PT. Bintan Jaya Samudra is not applied perfectly, especially in the follow-up section (Act) because this company only gives bonuses to employees who manage to achieve the target but there is no punishment for employees who do not reach the target.